Heterogeneous composite bipolar plate, method for manufacturing the same, sealed assembly comprising the same and use thereof
Patent Information
- Application Number
- CN202611545828.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-10-08
- Publication Date
- 2026-11-03
AI Technical Summary
Existing sealing and encapsulation technologies for heterogeneous composite bipolar plates suffer from poor compatibility, insufficient interfacial bonding strength, poor sealing reliability, and high ion dissolution, failing to meet the long-term operation requirements of proton exchange membrane electrolysis for hydrogen production.
A micro-nano hierarchical texture is formed on the surface of the cathode graphite-based doped layer by pulsed near-infrared laser etching. Combined with segmented laser welding of olefin adhesive layer and plastic end frame, a triple bonding mechanism of nano-anchoring, micro-intercalation and adhesive-plastic molecular entanglement is formed to control the thermal deformation of the anode metal layer.
It improves the interfacial bonding strength, reduces the helium leakage rate, enhances sealing reliability, is suitable for long-term operation of PEM electrolyzers, and reduces material costs.
Smart Images

Figure CN123027601A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of electrode preparation technology, and specifically relates to heterogeneous composite bipolar plates and their preparation methods, sealing components containing them, and their applications. Background Technology
[0002] Proton exchange membrane (PEM) electrolysis of water for hydrogen production has become a core technology for green hydrogen production due to its fast response speed, high hydrogen purity, and adaptability to the fluctuation characteristics of renewable energy. Bipolar plates, as the core component of the PEM electrolyzer, perform multiple functions including electrical conductivity, thermal conductivity, gas-liquid distribution, and mechanical support. Their material and packaging costs account for 30% to 40% of the total cost of the fuel cell stack.
[0003] The current mainstream solution in the industry is an all-titanium bipolar plate. Although it can withstand the high oxidation and strong acidity conditions of the anode, the high cost of the precious metal coating and titanium substrate severely restricts the large-scale promotion of PEM electrolysis for hydrogen production. To reduce costs, the industry has proposed a heterogeneous composite bipolar plate approach: a thin titanium plate is used on the anode side to withstand high-potential oxidation, while a lower-cost graphite-based composite material is used on the cathode side to replace the titanium plate, which can reduce the material cost of the bipolar plate by more than 30%. However, there is still a significant technological gap in the sealing and encapsulation technology of this type of heterogeneous bipolar plate. (1) Poor compatibility of traditional packaging solutions: Existing fuel cell stacks mostly use rubber sealing rings for compression sealing, which has problems such as rubber aging, hydrogen embrittlement cracking, and leakage caused by uneven assembly clamping force under long-term operation. It cannot match the design life of PEM electrolyzers of more than 100,000 hours; and the sealing ring occupies a large space, which is not conducive to improving the power density of the fuel cell stack.
[0004] (2) There is no dedicated solution for existing laser welding technology: Existing bipolar plate laser welding technology is mainly for welding and forming pure titanium metal bipolar plates, or bonding pure graphite bipolar plates to plastic frames; there are no publicly reported solutions for laser transmission plastic welding of heterogeneous composite bipolar plates of "anode metal + cathode doped graphite". Due to the huge difference in thermal conductivity and thermal expansion coefficient of the two materials, directly using conventional welding processes is prone to problems such as thermal deformation and warping of the anode metal layer, insufficient interface bonding strength, and poor sealing reliability.
[0005] (3) The method of strengthening the graphite side interface is limited: existing graphite-plastic laser welding mostly adopts simple laser etching roughening treatment, which is used to uniformly etch homogeneous graphite materials, and can only form mechanical interlocking on a single scale, resulting in low upper limit of interface bonding strength; and there has never been a technical solution that utilizes the doped phase components inside the graphite matrix to achieve in-situ strengthening through selective laser action, so there is no corresponding technical inspiration.
[0006] (4) Insufficient adaptability of sealing materials to operating conditions: Ordinary hot melt adhesive membranes have a high ion dissolution rate in high-temperature deionized water environments. The precipitated metal ions and small organic molecules will contaminate the proton exchange membrane and catalyst, leading to the degradation of membrane electrode performance and failing to meet the high-purity water operating conditions requirements of PEM hydrogen production.
[0007] In summary, there is an urgent need to develop a dedicated laser transmission welding solution that is compatible with heterogeneous composite bipolar plate structures and has high connection strength, high sealing reliability and low ion dissolution characteristics, in order to support the cost reduction, implementation and mass production of PEM water electrolysis hydrogen production bipolar plates. Summary of the Invention
[0008] This application provides a heterogeneous composite bipolar plate and its preparation method, a sealing assembly containing the same, and its applications, solving the following problems: 1. Solve the problem of thermal deformation of the metal layer and large residual stress at the interface caused by the mismatch of the thermal properties of the two materials during laser welding of heterogeneous composite bipolar plates (anode metal + cathode doped graphite); 2. To address the shortcomings of existing laser texturing on graphite surfaces, which can only achieve single-scale mechanical interlocking and have insufficient interfacial bonding strength, a reinforcement scheme is provided that utilizes the in-situ formation of nano-anchoring by the matrix doped phase. 3. Solves the problems of high ion dissolution and easy contamination of membrane electrodes in conventional hot melt adhesive membranes, and is suitable for long-term operation of PEM hydrogen production for high-purity water. 4. Fill the technological gap in the field of PEM hydrogen production by laser transmission welding of heterogeneous composite bipolar plates and plastic end frames, and provide a set of highly reliable packaging processes that can be mass-produced.
[0009] The first objective of this application is to provide a heterogeneous composite bipolar plate, comprising a stacked composite anode metal conductive layer and a cathode graphite-based doped layer; The cathode graphite-based doped layer uses graphite as the matrix and resin as the binder phase, with metal carbide dopants uniformly dispersed inside. The sealing welding surface of the cathode graphite-based doped layer has a micro-nano hierarchical texture, which includes micron-level anchoring pits and flow-guiding trenches connecting adjacent anchoring pits. Doped phase protrusions are distributed in situ on the surfaces of the anchoring pits and flow-guiding trenches.
[0010] In a specific embodiment of this application, the micro-nano hierarchical texture is obtained by etching the surface of a graphite-based doped layer preform using a pulsed near-infrared laser.
[0011] This application utilizes the characteristic that metal carbide dopant has a higher absorption rate for near-infrared lasers than the graphite matrix, achieving selective ablation of the graphite matrix in pit and groove regions. This exposes the metal carbide dopant phase in situ, resulting in a micro / nano hierarchical texture. Furthermore, the nanoscale morphology of these doped phase protrusions is generated synchronously during the pulsed near-infrared laser scanning process, specifically through the in-situ exposure of metal carbide particles after selective laser ablation of the surrounding graphite matrix.
[0012] In a specific embodiment of this application, the anchoring recess is inverted cone or dovetail shaped, with a depth of 6 to 180 μm, an opening diameter of 70 to 130 μm, and a center-to-center distance of 150 to 300 μm between two adjacent anchoring recesses. And / or, the depth of the guide trench is 8–22 μm and the width is 15–35 μm; And / or, the height of the doped phase protrusion is 200–800 nm.
[0013] In a specific embodiment of this application, the thickness of the cathode graphite-based doped layer is 1.5–3 mm; And / or, the metal carbide is one or more of titanium carbide, niobium carbide, and tungsten carbide; And / or, the mass ratio of the metal carbide doped phase to the graphite matrix is 5% to 15%.
[0014] In a specific embodiment of this application, the anode metal conductive layer is a pure titanium plate or a titanium alloy plate with a thickness of 0.8 to 2 mm.
[0015] In a specific embodiment of this application, the resin used in the cathode graphite-based doped layer is a bonding resin well known in the art, for example, epoxy resin.
[0016] The second objective of this application is to provide a method for preparing a heterogeneous composite bipolar plate, comprising: Preparation of composite substrate: The anode metal conductive layer and the cathode graphite-based doped layer are stacked to obtain the composite substrate; the cathode graphite-based doped layer has graphite as the matrix and resin as the binder phase, and metal carbide doped phase is uniformly dispersed inside. Preparation of in-situ micro-nano texture on the welding surface: The sealed welding surface of the cathode graphite-based doped layer in the composite substrate is scanned by pulsed near-infrared laser, and micron-level anchoring pits and flow-guiding trenches connecting the anchoring pits are etched and formed simultaneously. The metal carbide doped phase is exposed on the surface of the anchoring pits and flow-guiding trenches to generate doped phase protrusions and nano-morphology, thus obtaining a heterogeneous composite bipolar plate.
[0017] In a specific embodiment of this application, the wavelength of the pulsed near-infrared laser is 808–1064 nm.
[0018] In a specific embodiment of this application, the parameters of the pulsed near-infrared laser are: laser power 8-20W, scanning speed 60-160mm / s, and pulse frequency 20-50kHz.
[0019] In a specific embodiment of this application, prior to the step of "preparation of in-situ micro / nano texture on the welding surface", the method further includes: sealing surface pretreatment, including: A silane coupling agent is applied to the sealing welding surface of the cathode graphite-based doped layer of the composite substrate, and after curing, a coupling agent transition layer is formed.
[0020] In a specific embodiment of this application, the thickness of the silane coupling agent transition layer is 0.5–3 μm.
[0021] In specific embodiments of this application, the silane coupling agent is an epoxy silane or a vinyl silane.
[0022] The third objective of this application is to provide a heterogeneous composite bipolar plate-end frame integrated sealing assembly, comprising: the aforementioned heterogeneous composite bipolar plate and a plastic end frame; The heterogeneous composite bipolar plate and the plastic end frame are fixedly connected by an olefin adhesive layer. The olefin adhesive layer fills the anchoring pits and / or channeling grooves of the micro-nano hierarchical texture in the heterogeneous composite bipolar plate to form an anchoring structure. The anchoring structure and the doped phase protrusion form a mechanical interlock.
[0023] In a specific embodiment of this application, the olefin adhesive layer is formed by curing a carbon black modified polyolefin hot melt adhesive film. The carbon black modified polyolefin hot melt adhesive film uses maleic anhydride grafted polypropylene as the matrix resin and is doped with 2% to 6% of nano carbon black and 1% to 3% of polytetrafluoroethylene micro powder by weight of the matrix resin. And / or, the thickness of the olefin adhesive layer is 80–200 μm; And / or, the total ion dissolution of the olefin adhesive layer after soaking in deionized water at 80°C for 30 days is ≤0.5μg / cm2.
[0024] The fourth objective of this application is to provide a method for preparing a heterogeneous composite bipolar plate-end frame integrated sealing assembly, comprising: Adhesive film laying and alignment: An olefin adhesive film with a micro-nano hierarchical texture is laid on the sealing welding surface of the heterogeneous composite bipolar plate; and the pre-positioning is completed after aligning the sealing path; Pre-pressing and shaping: The adhesive film of the stacked heterogeneous composite bipolar plate and olefin adhesive layer is subjected to hot pressing treatment to initially fill the pores of the micro-nano hierarchical texture and dissipate most of the air at the interface, thus completing the pre-pressing and shaping of the adhesive film. Transmission laser segmented welding: A plastic end frame is placed over a pre-attached adhesive film, and clamping pressure is applied to ensure that the plastic end frame, adhesive film, and heterogeneous composite bipolar plate are tightly bonded together; a laser beam enters from one side of the plastic end frame, penetrates the plastic end frame, and acts on the adhesive film interface to perform segmented welding; during the segmented welding process, a heat dissipation fixture is set on the back side of the anode metal conductive layer in the heterogeneous composite bipolar plate to control the temperature of the anode metal conductive layer; Pressure holding and cooling molding: Welding is stopped, and the clamping pressure is maintained to cool to room temperature to form a heterogeneous composite bipolar plate-end frame integrated sealing assembly.
[0025] In a specific embodiment of this application, the parameters for pre-pressing and bonding are: hot pressing temperature 85-100℃, pressing pressure 0.4-0.9MPa, and holding time 20-40s; And / or, after the pre-pressing and bonding, the initial filling rate of the olefin adhesive film for the micro-nano hierarchical texture is ≥65%.
[0026] In a specific embodiment of this application, the segmented welding includes a preheating and wetting stage welding using a first power and a main welding stage welding using a second power, wherein the first power is lower than the second power; to ensure the following effect: Preheating with a lower initial power fully melts the olefin adhesive film, which is then evenly spread and completely filled with the micro-nano hierarchical texture via guiding channels. This forms a mechanical interlocking with the doped phase protrusions, creating a dual anchoring structure with interfacial adsorption. The power is then increased to a higher second power to melt the contact surface layer of the plastic end frame, forming a molecularly entangled molten transition layer with the hot-melt adhesive film. This makes the sealing connection between the heterogeneous composite bipolar plate and the plastic end frame more reliable and secure, ensuring that the helium leakage rate of the sealing assembly is ≤1×10⁻¹⁰ Pa. m 3 / s.
[0027] In a specific embodiment of this application, the heat dissipation fixture is a water-cooled copper plate, and during the segmented welding process, the heat dissipation fixture is in close contact with the back of the anode metal conductive layer.
[0028] In a specific embodiment of this application, the process parameters for the preheating and wetting stage are as follows: 8-18W pulsed near-infrared laser scanning is used, the scanning speed is 80-150mm / s, and the pulse frequency is 20-50kHz. And / or, the process parameters for the main welding stage are: increasing the laser power to 22-45W, the scanning speed to 50-100mm / s, and the pulse frequency to 30-60kHz.
[0029] In some embodiments of this application, the laser wavelength is 808–1064 nm during the segmented welding process.
[0030] In a specific embodiment of this application, the temperature of the anode metal conductive layer is ≤110℃; And / or, the plastic end frame is made of polypropylene or glass fiber reinforced polypropylene. And / or, during the segmented laser welding process, high-frequency ultrasonic vibration of 25 to 40 kHz is simultaneously applied to the welding area, with a vibration amplitude of 5 to 5 μm.
[0031] The fifth objective of this application is to provide the application of the aforementioned heterogeneous composite bipolar plate-end frame integrated sealing assembly in a proton exchange membrane water electrolysis hydrogen production stack.
[0032] Compared with the prior art, this application has the following advantages: This application discloses a heterogeneous composite bipolar plate, its preparation method, a sealing assembly comprising the same, and its applications. The sealing welding surface of the cathode graphite-based doped layer in the heterogeneous composite bipolar plate has a micro-nano hierarchical texture. This micro-nano hierarchical texture (including micron-level anchoring pits and channeling trenches connecting adjacent anchoring pits, with doped phase protrusions in situ distributed on the surfaces of the anchoring pits and channeling trenches) provides a hierarchical interlocking structure for the electrode sealing joint. The anchoring pits and channeling trenches provide micron-level accommodating space, while the doped phase protrusions provide a nano-level embedding structure. Furthermore, the anchoring structure within the micron-level accommodating space and the doped phase protrusions form a mechanical lock, resulting in a joint shear strength increase of over 60% compared to ordinary homogeneous etching. This effect is beyond the expectations of those skilled in the art and possesses outstanding substantial characteristics.
[0033] In addition, this application has the following advantages: (1) The innovative in-situ selective etching enhancement mechanism for doped phases is remarkable: This application ingeniously utilizes the metal carbide doped phase contained in the graphite-based doped layer of the heterogeneous composite bipolar cathode. Based on the difference in absorption rate of the metal carbide phase and the graphite matrix to near-infrared laser, selective ablation is achieved through pulsed laser, exposing the metal carbide particles in situ on the sealed welding surface of the graphite-based doped layer to form a micro-nano hierarchical texture. This design breaks through the limitation that traditional laser etching of homogeneous materials can only form a single morphology, upgrading the interface anchoring from "micron-level macroscopic interlocking" to hierarchical interlocking of "micron-level pits + nano-level protrusions".
[0034] (2) A triple bonding mechanism is constructed, comprehensively improving sealing and mechanical properties: This application forms a triple interface bonding mechanism of "doped phase nano-anchoring + micro-textured mechanical interlocking + adhesive-plastic molecular interfusion": nano-protrusions provide microscale interlocking and interfacial adsorption, micron-sized pits provide macroscopic anti-peeling anchoring force, and molecular entanglement between the adhesive layer and the plastic end frame ensures a homogeneous transition. Compared with traditional planar adhesive bonding, the joint shear strength is increased by more than 1.5 times, the helium leakage rate is reduced by 2 orders of magnitude, and the strength retention rate after immersion in 80℃ deionized water for 30 days is more than 93%, which can fully meet the long-term sealing operation requirements of PEM electrolytic cells.
[0035] (3) Exclusive back-side temperature control process to solve the problem of deformation during welding of heterogeneous materials: In response to the unique problem of large differences in thermal conductivity and coefficient of thermal expansion between the two sides of heterogeneous composite bipolar plates, this application has designed a back-side water-cooling heat dissipation process for the anode metal layer, which controls the maximum temperature of the metal layer during welding to within 120°C, and keeps the thermal deformation of the metal layer below 0.05mm, thus avoiding problems such as decreased assembly accuracy and increased contact resistance caused by warping deformation. This design is an exclusive and necessary technical feature for welding heterogeneous composite bipolar plates, and there are no corresponding technical requirements or inspirations for welding pure graphite or pure metal bipolar plates.
[0036] (4) Low-dissolution film system, suitable for hydrogen production specific operating conditions: The carbon black modified PP-g-MAH film system used in this application, through polytetrafluoroethylene micropowder doping and high-purity matrix formulation, controls the total ion dissolution amount to 0.5 μg / cm³ after soaking in deionized water at 80℃ for 30 days. 2 Within this range, it avoids contamination of the proton exchange membrane and catalyst by the precipitates of the adhesive layer, and matches the high-purity water operation conditions of PEM hydrogen production from a material perspective, which is different from general industrial welding adhesive membranes.
[0037] (5) Strong process compatibility, supporting mass production and cost reduction: The process of this application is directly compatible with existing laser welding production lines without the need for new large-scale equipment; combined with the cost reduction advantage of heterogeneous composite bipolar plates, the overall cost of single cell packaging can be reduced by more than 25%, which has extremely strong industrialization value.
[0038] Other features and advantages of this application will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the application. The objectives and other advantages of this application may be realized and obtained by means of the structures pointed out in the description, claims and drawings. Attached Figure Description
[0039] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0040] Figure 1 A schematic diagram of the structure of a heterogeneous composite bipolar plate according to certain embodiments of this application is shown; Figure 2 The image shows an optical micrograph of the square micro / nano hierarchical texture of the cathode graphite-based doped layer according to certain embodiments of this application. The upper side shows the low-magnification overall array morphology, and the lower side shows the high-magnification microstructure of a single anchoring pit. Figure 3 Optical micrographs of the striped flow channel texture of the cathode graphite-based doped layer according to certain embodiments of this application are shown. Figure 4 This paper shows a schematic diagram of a longitudinal section after the cathode graphite-based doped layer is welded to the plastic end frame according to certain embodiments of this application; Figure 5 A flowchart illustrating the steps according to certain embodiments 1 of this application is shown; Figure 6 This paper shows a physical observation image of the micro / nano textured interface after pre-compression according to certain embodiments 1 of this application; In the figure: 10, anode metal conductive layer; 20, cathode graphite-based doped layer; 21, doped phase protrusion; 30, plastic end frame; 31, olefin adhesive layer; 311, anchoring structure. Detailed Implementation
[0041] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0042] like Figure 1 As shown, a heterogeneous composite bipolar plate according to certain embodiments of this application includes a stacked composite anode metal conductive layer 10 and a cathode graphite-based doped layer 20. The cathode graphite-based doped layer 20 uses graphite as the matrix and resin as the binder phase, and has metal carbide doped phases uniformly dispersed inside. The sealing and welding surface of the cathode graphite-based doped layer 20 has a micro-nano hierarchical texture, which includes micron-scale anchoring pits (see details). Figure 2 ), and the guide channel connecting adjacent anchoring pits (see details) Figure 3 The anchoring pits and the surface of the guiding trenches are in situ distributed with doped phase protrusions 21 (see details). Figure 4 ).
[0043] like Figure 1 As shown, a heterogeneous composite bipolar plate-end frame integrated sealing assembly according to certain embodiments of this application includes: the heterogeneous composite bipolar plate and the plastic end frame 30; The heterogeneous composite bipolar plate and the plastic end frame 30 are fixedly connected by an olefin adhesive layer 31. The olefin adhesive layer 31 fills the micro-nano hierarchical texture (anchoring pits and / or channeling grooves) in the heterogeneous composite bipolar plate to form an anchoring structure 311. The anchoring structure 311 and the doped phase protrusion 21 form a mechanical interlock, further stabilizing the connection between the heterogeneous composite bipolar plate and the plastic end frame 30.
[0044] Example 1: Welding process of titanium carbide-doped isostatically pressed graphite heterocomposite bipolar plates, detailed process is as follows. Figure 5 ,include: 1. Preparation of heterogeneous composite bipolar plates: (1) Heterogeneous composite substrate: The anode metal conductive layer is a 1mm thick industrial pure titanium plate (TA1), and the cathode graphite-based doped layer is a 2mm thick isostatically pressed graphite-based doped layer; the graphite matrix uses phenolic resin as the binder phase and is doped with titanium carbide (TiC) particles accounting for 8wt% of the graphite matrix, with a particle size of 1-3μm; the effective size of the bipolar plate is 300mm×400mm, and the width of the sealing welding surface is 12mm. The anode metal conductive layer and the cathode graphite-based doped layer are stacked together; (2) In-situ micro / nano texture fabrication: The sealed welding surface of the cathode graphite-based doped layer was etched using pulsed near-infrared light with a wavelength of 915 nm. The etching pattern consisted of inverted conical anchoring pits and mesh-like guiding trenches. During the pulsed near-infrared light etching scan, the etching was performed along the preset pattern, and the scan was stopped after completing one lap. The anchoring pits had a depth of 120 μm, an opening diameter of 100 μm, and a center-to-center distance of 200 μm between two adjacent anchoring pits. The guiding trenches had a depth of 15 μm, a width of 25 μm, and connected adjacent pits. Because TiC has a higher absorption rate for 915 nm laser than graphite, TiC nano-protrusions were exposed in situ on the inner wall of the pits after laser ablation, with a protrusion height of 300–500 nm. The parameters of the pulsed near-infrared laser were: laser power 12 W, scanning speed 80 mm / s, and pulse frequency 25 kHz.
[0045] 2. Preparation of integrated sealing components: (1) Alignment of olefin adhesive layer: Low-dissolution carbon black modified PP-g-MAH adhesive film, film thickness 120μm, the amount of nano carbon black added in the carbon black modified PP-g-MAH adhesive film (accounting for 4wt% of the mass of PP-g-MAH matrix) and the amount of PTFE micro powder added (accounting for 2wt% of the mass of PP-g-MAH matrix) are 0.32μg / cm. The total ion dissolution of the carbon black modified PP-g-MAH adhesive film after soaking in deionized water at 80℃ for 30 days is 0.32μg / cm. 2 After aligning the sealing path, the pre-positioning is completed; the total ion dissolution amount is measured by ICP-MS immersion method (the same below).
[0046] (2) Plastic end frame: 15wt% glass fiber reinforced polypropylene (PP-GF15) end frame, 3mm thick.
[0047] (3) Pre-pressing and shaping: The adhesive film is precisely laid on the welding surface of the micro-nano texture and pre-pressed using a flatbed hot press at a temperature of 95℃ and a pressure of 0.6MPa for 30s. The initial filling rate of the adhesive film on the texture is approximately 72%. The image after pre-pressing is shown below. Figure 6 As shown.
[0048] (4) Clamping and alignment: Cover the PP-GF15 end frame over the adhesive film, align the special tooling with the sealing path, and apply a clamping pressure of 0.5MPa; attach the back of the anode titanium plate to the water-cooled copper plate heat dissipation tooling (water-cooled copper plate).
[0049] (5) Segmented laser welding: A 915nm pulsed laser is incident from the end frame side of the PP-GF15; the power of the preheating stage is 12W, the scanning speed is 100mm / s, and the pulse frequency is 30kHz. During welding, the laser scans around the end frame of the PP-GF15 and then stops. The power of the main welding stage is 35W, the scanning speed is 70mm / s, and the pulse frequency is 40kHz. During welding, the laser scans around the end frame of the PP-GF15 and then stops. The wavelength is the same as that of the preheating stage. The maximum temperature of the back side of the anode titanium plate is 102℃ throughout the welding process.
[0050] (6) Pressure holding and cooling: After stopping the laser output, maintain the clamping pressure for 10 seconds and allow it to cool naturally to room temperature to obtain an integrated sealing component.
[0051] Example 2: Welding of niobium carbide-doped molded graphite heterocomposite bipolar plates (low-cost solution) 1. Preparation of heterogeneous composite bipolar plates: (1) Heterogeneous composite substrate: The anode metal conductive layer is a 1.2mm thick Ti-0.2Pd titanium alloy plate, and the cathode graphite-based doped layer is a 2.5mm thick molded graphite-based doped layer; the graphite matrix uses epoxy resin as the binder phase and is doped with 12wt% niobium carbide (NbC) particles, with a particle size of 2-4μm; the effective size of the bipolar plate is 350mm×450mm, and the width of the sealing welding surface is 15mm. The anode metal conductive layer and the cathode graphite-based doped layer are stacked together; (2) In-situ fabrication of micro / nano textures: Pulsed fiber laser etching with a wavelength of 1064 nm was used. The etching pattern consisted of dovetail-shaped anchoring pits and dendritic channeling trenches. During near-infrared laser etching, the etching was performed along the preset pattern, and the scanning was stopped after one lap. The anchoring pits had a depth of 150 μm, an opening diameter of 120 μm, and a center-to-center distance of 250 μm between two adjacent anchoring pits. The channeling trenches had a depth of 20 μm and a width of 30 μm. After selective laser ablation, NbC nanoprotrusions were exposed in situ on the surface of the pits, with a protrusion height of 400–700 nm. The parameters of the pulsed near-infrared laser were: laser power 12 W, scanning speed 120 mm / s, and pulse frequency 30 kHz.
[0052] 2. Preparation of integrated sealing components: (1) Alignment of olefin adhesive layer: Low-dissolution carbon black modified PP-g-MAH adhesive film, film thickness 150μm, the amount of nano carbon black added in the carbon black modified PP-g-MAH adhesive film (accounting for 5wt% of the PP-g-MAH matrix mass) and the amount of PTFE micro powder added (accounting for 2.5wt% of the PP-g-MAH matrix mass) are 0.28μg / cm. The total ion dissolution of the carbon black modified PP-g-MAH adhesive film after soaking in deionized water at 80℃ for 30 days is 0.28μg / cm. 2 After aligning the sealing path, the pre-positioning is completed.
[0053] (2) Plastic end frame: 20% glass fiber reinforced polypropylene (PP-GF20) end frame, 3.5mm thick.
[0054] (3) Pre-pressing and shaping: hot pressing temperature 90℃, pressure 0.7MPa, holding pressure for 35s, the initial filling rate of the adhesive film is about 76%.
[0055] (4) Clamping and alignment: PP-GF20 end frame clamping, clamping pressure 0.6MPa; anode side equipped with water cooling heat dissipation fixture (water cooling heat dissipation copper plate).
[0056] (5) Segmented laser welding: A 1064nm pulsed laser is incident from the side of the PP-GF20 end frame; the power of the preheating stage is 15W, the scanning speed is 120mm / s, and the pulse frequency is 35kHz. During welding, the laser scans around the PP-GF15 end frame and then stops scanning; the power of the main welding stage is 40W, the scanning speed is 80mm / s, and the pulse frequency is 45kHz. During welding, the laser scans around the PP-GF15 end frame and then stops scanning. The wavelength is the same as the wavelength of the preheating stage; the maximum temperature of the back side of the anode titanium alloy is 108℃ throughout the welding process.
[0057] (6) Pressure holding and cooling: After holding the pressure for 12 seconds, the product is naturally cooled and shaped.
[0058] Example 3: Welding process of epoxy-silane pretreated titanium carbide-doped graphite heterocomposite bipolar plates 1. Preparation of heterogeneous composite bipolar plates: (1) Heterogeneous composite substrate: The anode metal conductive layer is a 1mm thick industrial pure titanium plate (TA1), and the cathode graphite-based doped layer is a 2mm thick isostatically pressed graphite-based doped layer; the graphite matrix uses epoxy resin as the binder phase and is doped with titanium carbide (TiC) particles accounting for 8wt% of the graphite matrix, with a particle size of 1~3μm; the effective size of the bipolar plate is 300mm×400mm, and the width of the sealing welding surface is 12mm. The anode metal conductive layer and the cathode graphite-based doped layer are stacked to obtain the composite substrate.
[0059] (2) Pretreatment of sealing surface: The sealing welding surface of the cathode graphite-based doped layer of the composite substrate is coated with silane coupling agent. Epoxy silane (γ-glycidoxypropyltrimethoxysilane) is used to prepare a 5% (v / v) silane ethanol-water solution, which is uniformly coated onto the sealing welding surface by spraying. After standing at room temperature for 5 min, it is placed in a 120℃ oven for curing for 30 min, forming a coupling agent transition layer with a thickness of approximately 1.2 μm.
[0060] (3) In-situ micro / nano texture fabrication: The sealed welding surface with a coupling agent transition layer was etched using a pulsed fiber laser with a wavelength of 915 nm. The etched pattern consisted of inverted conical anchoring pits and mesh-like guiding trenches. During near-infrared laser etching, the process proceeded along the preset etched pattern, and the scanning was stopped after completing one lap. The anchoring pits were 120 μm deep, with an opening diameter of 100 μm and a center-to-center distance of 200 μm between adjacent anchoring pits. The guiding trenches were 15 μm deep and 25 μm wide, connecting adjacent pits. Because TiC has a higher absorption rate for 915 nm laser than graphite, TiC nano-protrusions were exposed in situ on the inner wall of the pits after laser ablation, with a protrusion height of 300~500 nm. The process parameters for the pulsed near-infrared laser were: laser power 12 W, scanning speed 80 mm / s, and pulse frequency 25 kHz.
[0061] 2. Preparation of integrated sealing components: (1) Alignment of olefin adhesive layer: Low-dissolution carbon black modified PP-g-MAH adhesive film, adhesive film thickness 120μm, carbon black modified PP-g-MAH adhesive film added amount of 4wt% (accounting for PP-g-MAH matrix mass) and PTFE micro powder added amount of 2wt% (accounting for PP-g-MAH matrix mass); carbon black modified PP-g-MAH adhesive film soaked in deionized water at 80℃ for 30 days with total ion dissolution amount of 0.31μg / cm², the adhesive film is laid by aligning the sealing path using positioning tooling to complete the pre-positioning.
[0062] (2) Plastic end frame: 15wt% glass fiber reinforced polypropylene (PP-GF15) end frame, 3mm thick.
[0063] (3) Pre-pressing and shaping: The adhesive film is precisely laid on the welding surface of the micro-nano texture and pre-pressed using a flat hot press at a temperature of 95℃ and a pressure of 0.6MPa for 30s. The initial filling rate of the adhesive film on the texture is about 74%.
[0064] (4) Clamping and alignment: Cover the PP-GF15 end frame over the adhesive film, align the special tooling with the sealing path, and apply a clamping pressure of 0.5MPa; the back of the anode titanium plate is attached to the water-cooled copper plate heat dissipation tooling.
[0065] (5) Segmented laser welding: A 915nm pulsed laser is incident from the end frame side of the PP-GF15; the power of the preheating and wetting stage is 12W, the scanning speed is 100mm / s, and the pulse frequency is 30kHz. During welding, the laser scans around the PP-GF15 end frame and then stops. The power of the main welding stage is 35W, the scanning speed is 70mm / s, and the pulse frequency is 40kHz. During welding, the laser scans around the PP-GF15 end frame and then stops. The wavelength is the same as that of the preheating stage. The maximum temperature of the back side of the anode titanium plate is 101℃ throughout the welding process.
[0066] (6) Pressure holding and cooling: After stopping the laser output, maintain the clamping pressure for 10 seconds and allow it to cool naturally to room temperature to obtain an integrated sealed component.
[0067] Scale settings (1) Comparative Example 1 aims to provide an integrated sealing assembly: compared with Example 1, the cathode graphite layer surface is not etched and remains a smooth plane, and the rest is the same as Example 1.
[0068] (2) Comparative Example 2 aims to provide an integrated sealing assembly: compared with Example 1, pure graphite (without metal carbide doping) is used as the cathode plate, and the rest is the same as Example 1.
[0069] (3) Comparative Example 3 aims to provide an integrated sealing assembly: Compared with Example 1, the segmented laser welding step is changed to a one-step laser scanning with a laser wavelength of 915nm. Other parameters are: power 35W, scanning speed 70mm / s, pulse frequency 40kHz. Welding is performed with one scan, and the rest is the same as Example 1.
[0070] (4) Comparative Example 4 aims to provide an integrated sealing assembly: compared with Example 1, the back-side cooling process of the anode-side metal plate is eliminated, and the rest is the same as Example 1.
[0071] Test Example: Performance tests were conducted on the integrated sealing assemblies provided in Examples 1-2 and Comparative Examples 1-3. The test results are shown in Table 1. The performance testing standards and methods involved are as follows: (1) Shear strength: The tensile shear test was carried out using a universal electronic testing machine in accordance with the GB / T7124 standard. The tensile speed was 5 mm / min. Five samples were tested in each group and the average value was taken. The shear strength was recorded as a0.
[0072] (2) Helium leakage rate: The helium leakage rate of the sealed weld was tested using a helium mass spectrometer at a pressure difference of 0.2 MPa, and the helium leakage rate was recorded as b.
[0073] (3) Deionized water immersion test: The welding sample is immersed in deionized water at 80℃ for 30 days. After drying, the shear strength is tested, the strength retention rate is calculated, and the corresponding test result is recorded as c.
[0074] (4) Thermal cycling test: 100 thermal cycles were performed in the range of -40℃ to 120℃, and each temperature point was kept at the temperature for 30 minutes. After the cycle, the shear strength was tested, the strength retention rate was calculated, and the corresponding test results were recorded as e.
[0075] (5) Anode layer deformation: The difference in flatness of the anode metal layer surface before and after welding is measured by a coordinate measuring machine and is taken as the maximum thermal deformation. The maximum thermal deformation is recorded as f.
[0076] Table 1
[0077] As shown in Table 1 of the test results: (1) Compared with the comparative example 2 of pure graphite homogeneous etching, the embodiments of this application utilize nano-anchors formed in situ by doped phases to increase shear strength by more than 60% and improve sealing level by 1 to 2 orders of magnitude. It is not a simple superposition of "laser etching + adhesive bonding" and has unexpected technical effects.
[0078] (2) The segmented welding scanning process can effectively control the melting and secondary flow anchoring of the adhesive film, and increase the shear strength by more than 25%. The "preheating" has better sealing reliability and impact resistance stability.
[0079] (3) The back-side temperature control process controls the deformation of the anode metal layer to within 0.05mm, which solves the unique pain point of thermal deformation mismatch in the welding of heterogeneous composite bipolar plates. It is an exclusive optimization that cannot be covered by general welding solutions.
[0080] (4) The strength retention rate of the proposed solution exceeds 90% under long-term deionized water immersion and hot and cold cycle conditions, which can fully meet the requirements of long-term stable operation of PEM electrolyzer.
[0081] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A heterogeneous composite bipolar plate, characterized in that, It includes a stacked composite anode metal conductive layer and a cathode graphite-based doped layer; The cathode graphite-based doped layer uses graphite as the matrix and resin as the binder phase, with metal carbide dopants uniformly dispersed inside. The sealing welding surface of the cathode graphite-based doped layer has a micro-nano hierarchical texture, which includes micron-level anchoring pits and flow-guiding trenches connecting adjacent anchoring pits. Doped phase protrusions are distributed in situ on the surfaces of the anchoring pits and flow-guiding trenches.
2. The heterogeneous composite bipolar plate according to claim 1, characterized in that, The micro-nano hierarchical texture is obtained by etching the surface of a graphite-based doped layer preform using a pulsed near-infrared laser.
3. The heterogeneous composite bipolar plate according to claim 1, characterized in that, The anchoring pit is inverted cone or dovetail shaped, with a depth of 6 to 180 μm, an opening diameter of 70 to 130 μm, and a center-to-center distance of 150 to 300 μm between two adjacent anchoring pits. And / or, the depth of the guide trench is 8–22 μm and the width is 15–35 μm; And / or, the height of the doped phase protrusion is 200–800 nm; And / or, the thickness of the cathode graphite-based doped layer is 1.5–3 mm; And / or, the metal carbide is one or more of titanium carbide, niobium carbide, and tungsten carbide; And / or, the mass ratio of the metal carbide doped phase to the graphite matrix is 5% to 15%.
4. A heterogeneous composite bipolar plate according to any one of claims 1-3, characterized in that, The anode metal conductive layer is a pure titanium plate or a titanium alloy plate with a thickness of 0.8 to 2 mm.
5. The method for preparing a heterogeneous composite bipolar plate according to claim 1, characterized in that, include: Preparation of composite substrate: The anode metal conductive layer and the cathode graphite-based doped layer are stacked to obtain the composite substrate; the cathode graphite-based doped layer has graphite as the matrix and resin as the binder phase, and metal carbide doped phase is uniformly dispersed inside. Preparation of in-situ micro-nano texture on the welding surface: The sealed welding surface of the cathode graphite-based doped layer in the composite substrate is scanned by pulsed near-infrared laser, and micron-level anchoring pits and flow-guiding trenches connecting the anchoring pits are etched and formed simultaneously. The metal carbide doped phase is exposed on the surface of the anchoring pits and flow-guiding trenches to generate doped phase protrusions and nano-morphology, thus obtaining a heterogeneous composite bipolar plate.
6. The method for preparing a heterogeneous composite bipolar plate according to claim 5, characterized in that, The wavelength of the pulsed near-infrared laser is 808–1064 nm; And / or, the parameters of the pulsed near-infrared laser are: laser power 8-20W, scanning speed 60-160mm / s, and pulse frequency 20-50kHz.
7. The method for preparing a heterogeneous composite bipolar plate according to claim 5, characterized in that, Before the step of "preparation of in-situ micro / nano textures on the welding surface", the following is also included: sealing surface pretreatment, including: A silane coupling agent is applied to the sealing welding surface of the cathode graphite-based doped layer of the composite substrate, and after curing, a coupling agent transition layer is formed.
8. The method for preparing a heterogeneous composite bipolar plate according to claim 7, characterized in that, The thickness of the silane coupling agent transition layer is 0.5–3 μm.
9. The method for preparing a heterogeneous composite bipolar plate according to claim 7, characterized in that, The silane coupling agent is an epoxy silane or a vinyl silane.
10. A heterogeneous composite bipolar plate-end frame integrated sealing assembly, characterized in that, include: A heterogeneous composite bipolar plate and a plastic end frame as described in any one of claims 1-4; The heterogeneous composite bipolar plate and the plastic end frame are fixedly connected by an olefin adhesive layer. The olefin adhesive layer fills the anchoring pits and / or channeling grooves of the micro-nano hierarchical texture in the heterogeneous composite bipolar plate to form an anchoring structure. The anchoring structure and the doped phase protrusion form a mechanical interlock.
11. The heterogeneous composite bipolar plate-end frame integrated sealing assembly according to claim 10, characterized in that, The olefin adhesive layer is formed by curing carbon black modified polyolefin hot melt adhesive film. The carbon black modified polyolefin hot melt adhesive film uses maleic anhydride grafted polypropylene as the matrix resin and is doped with 2% to 6% of nano carbon black and 1% to 3% of polytetrafluoroethylene micro powder by weight of the matrix resin. And / or, the thickness of the olefin adhesive layer is 80–200 μm; And / or, the total ion dissolution of the olefin adhesive layer after soaking in deionized water at 80°C for 30 days is ≤0.5 μg / cm³. 2 .
12. A method for preparing a heterogeneous composite bipolar plate-end frame integrated sealing assembly, characterized in that, include: Adhesive film laying alignment: An olefin adhesive film is laid on the sealing and welding surface with micro-nano hierarchical texture in a heterogeneous composite bipolar plate; And complete the pre-positioning after aligning the sealing path; Pre-pressing and shaping: The adhesive film of the stacked heterogeneous composite bipolar plate and olefin adhesive layer is subjected to hot pressing treatment to initially fill the pores of the micro-nano hierarchical texture and dissipate most of the air at the interface, thus completing the pre-pressing and shaping of the adhesive film. Transmission laser segmented welding: A plastic end frame is placed over a pre-attached adhesive film, and clamping pressure is applied to ensure that the plastic end frame, adhesive film, and heterogeneous composite bipolar plate are tightly bonded together; a laser beam enters from one side of the plastic end frame, penetrates the plastic end frame, and acts on the adhesive film interface to perform segmented welding; during the segmented welding process, a heat dissipation fixture is set on the back side of the anode metal conductive layer in the heterogeneous composite bipolar plate to control the temperature of the anode metal conductive layer; Pressure holding and cooling molding: Welding is stopped, and the clamping pressure is maintained to cool to room temperature to form a heterogeneous composite bipolar plate-end frame integrated sealing assembly.
13. The method for preparing a heterogeneous composite bipolar plate-end frame integrated sealing assembly according to claim 12, characterized in that, The parameters for pre-pressing and bonding are: hot pressing temperature 85-100℃, pressing pressure 0.4-0.9MPa, and holding time 20-40s; And / or, after the pre-pressing and bonding, the initial filling rate of the olefin adhesive film for the micro-nano hierarchical texture is ≥65%.
14. A method for preparing a heterogeneous composite bipolar plate-end frame integrated sealing assembly according to any one of claims 12-13, characterized in that, The segmented welding includes a preheating and wetting stage welding using a first power and a main welding stage welding using a second power, wherein the first power is lower than the second power; And / or, the heat dissipation fixture is a water-cooled copper plate, and during the segmented welding process, the heat dissipation fixture is in close contact with the back of the anode metal conductive layer.
15. The method for preparing a heterogeneous composite bipolar plate-end frame integrated sealing assembly according to claim 14, characterized in that, The process parameters for the preheating and wetting stage are as follows: 8-18W pulsed near-infrared laser scanning is used, the scanning speed is 80-150mm / s, and the pulse frequency is 20-50kHz. And / or, the process parameters for the main welding stage are: increasing the laser power to 22-45W, the scanning speed to 50-100mm / s, and the pulse frequency to 30-60kHz. And / or, the temperature of the anode metal conductive layer is ≤110℃; And / or, the plastic end frame is made of polypropylene or glass fiber reinforced polypropylene. And / or, the helium leakage rate of the sealing assembly is ≤1×10⁻¹⁰ Pa. m 3 / s; And / or, during the segmented welding process, high-frequency ultrasonic vibration of 25 to 40 kHz is simultaneously applied to the welding area, with a vibration amplitude of 5 to 5 μm.
16. The application of the heterogeneous composite bipolar plate-end frame integrated sealing assembly according to claim 10 or 11 in a proton exchange membrane water electrolysis hydrogen production stack.
